Accountants’ Perspective In Inclusivity In Social Aspect - Ahalik Ahalik (JURNAL ONLINE INSAN AKUNTAN, 2016)
Abstract: Purpose – The purpose of this paper is to investigate the accountants’ perspective in inclusivity in social aspects that one of the goals in project of Sustainable Development Goals (SDG) in term of achieving sustainable development. Methodology – Questionnaire and content analysis methods were applied for the purpose of the study. A total 72 respondents of Indonesian accountants in year 2015 from 5 different category (public accountant, management accountant, education accountant, tax accountant, and government accountant) provided their perspective by ranking of understanding and importance in inclusivity in social aspect. Findings - It finds that perspective of accountants in understanding about inclusivity in social aspect is in the range of strong and very strong, also, the importance to get involved in social aspect is in the range of strong to very strong. The most findings are accountants stated that conquering the corruption is very important to achieve sustainable development through following ethical conduct, be responsible and transparent, obeying the rule, and becoming whistle blower in any unfair cases. Research limitations - This study is limited only discussing the goal number 16 about inclusivity in social aspects from 17 goals in SDG, also the respondents are only 72 accountants that domicile in Jakarta and surronded, not covering all accountants in Indonesia. Keywords: Corporate Social Responsibility (CSR), Sustainable Development, Sustainable Development Goals (SDG).